Rage, Delusion and Abolitionism: Contemporary British Society in the Eyes of Peter Hitchens (American & British Studies Annual, 2012)
The present article focuses on the work of contemporary British journalist and public intellectual, Peter Hitchens (b. 1951). Hitchens  represents one of the most vocal voices of modern British conservatism, his works included into syllabi of British Studies at several universities. The paper starts with a discussion of his specific “anti-conversion” in the context of his generation from a Trotskyite to a Tory, then concentrates on the major issues of his critique: the slow decline of traditional British values since the 1960s, failure of British politics, problematic developments in relation to law and order, cultural revolution and, finally, his views on new atheism, so aptly represented by his recently deceased brother Christopher (1949-2011). The article concludes with a short discussion of the significance of the use of his ideas in teaching courses on British society since the 1960s.
Keywords: Peter Hitchens; British society since the 1960s; conservatism; contemporary British politics; new atheism